Effectiveness of Health Education Family Planning Guidelines on Health Beliefs and Behaviours Regarding Family Planning Methods Among Married Men in Myanmar - Zay Yar Tun; Tintin Sukartini (Jurnal Ners, 2017)
Introduction: Males are the most important members and care-takers of the family, but they are considered to be uncooperative when it comes to the usage of family planning methods. Traditionally, family planning programs have focused primarily on women, and most of the methods are designed for women considering that it is the women who become pregnant and it is easy to deliver reproductive health services as part of maternal and child health programs. The main objective of this study was to study the effectiveness of Health Education (HE) Family Planning Guidelines on Health Belief and Behaviours regarding family planning methods among married menMethods: A quasi-experimental study design was used to compare the results of the effectiveness of health education on the health beliefs and behaviours regarding family planning methods among married men. Mann-Whitney test and Manova test were used to analyse the data.Results:  It was found that there was a difference of health belief with p= 0.038, knowledge with p= 0.000 and attitude with p= 0.000 between the treatment and control group.Conclusion: There was an impact on the improvement of health belief and behaviours regarding family planning methods in the study group which was significantly improved after intervention. As the predetermined hypothesis, a difference was found between the knowledge, attitude and health beliefs of the married men who received health education and those who did not receive health education.